Regulation of B cell functions by the sialic acid-bincing receptors Siglec-G and CD22 - Jellusova, Julia; Nitschke, Lars (Frontiers in Immunology, 2012)
B cell antigen receptor (BCR) engagement can lead to many different physiologic outcomes. To achieve an appropriate response, the BCR signal is interpreted in the context of other stimuli and several additional receptors on the B cell surface participate in the modulation of the signal. Two members of the Siglec (sialic acid-binding immunoglobulin-like lectin) family, CD22 and Siglec-G have been shown to inhibit the BCR signal. Recent findings indicate that the ability of these two receptors to bind sialic acids might be important to induce tolerance to self-antigens. Sialylated glycans are usually absent on microbes but abundant in higher vertebrates and might therefore provide an important tolerogenic signal. Since the expression of the specific ligands for Siglec-G and CD22 is tightly regulated and since Siglecs are not only able to bind their ligands in trans but also on the same cell surface this might provide additional mechanisms to control the BCR signal. Although both Siglec-G and CD22 are expressed on B cells and are able to inhibit BCR mediated signaling, they also show unique biological functions. While CD22 is the dominant regulator of calcium signaling on conventional B2 cells and also seems to play a role on marginal zone B cells, Siglec-G exerts its function mainly on B1 cells and influences their lifespan and antibody production. Both Siglec-G and CD22 have also recently been linked to toll-like receptor signaling and may provide a link in the regulation of the adaptive and innate immune response of B cells.
Keywords: Siglecs; B lymphocytes; BCR signaling; inhibitory signaling; TLR; autoimmunity; B1 cells